2018
DOI: 10.4317/medoral.22698
|View full text |Cite
|
Sign up to set email alerts
|

Dental developmental alterations in patients with dilacerated teeth

Abstract: BackgroundThe aim of this study was to record and analyze all DDAs associated to dilacerated teeth in patients attending the clinics of the Postgraduate Division, Facultad de Odontología, UNAM in Mexico City.Material and MethodsOrthopantomograms from all patients seeking for stomatological attention in our institution were reviewed and those cases of dilaceration were separated. Age, gender, diagnosis, location, involved teeth and associated DDAs were recorded and analyzed.ResultsFrom 6,340 patients, 99 (1.6%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Among the developmental disorders that had the greatest expression was root dilaceration with a total of 25.9% of the cases, being more prevalent in females, despite not having a statistically significant difference, these data were similar to those found by Ledesma-Montes et al, where they also correlated these alterations with other DDA 12 . Regarding the location 19.8% of the cases were in the mandible, a systematic review showed that the most affected teeth are the lower third and second molars, followed by upper premolars and upper incisors respectively, thus showing the highest frequency in the lower arch 7,13,14 .…”
Section: Discussionsupporting
confidence: 88%
“…Among the developmental disorders that had the greatest expression was root dilaceration with a total of 25.9% of the cases, being more prevalent in females, despite not having a statistically significant difference, these data were similar to those found by Ledesma-Montes et al, where they also correlated these alterations with other DDA 12 . Regarding the location 19.8% of the cases were in the mandible, a systematic review showed that the most affected teeth are the lower third and second molars, followed by upper premolars and upper incisors respectively, thus showing the highest frequency in the lower arch 7,13,14 .…”
Section: Discussionsupporting
confidence: 88%
“…According to Hamasha et al (2002), and Malcic et al (2006), a tooth is considered to have a dilaceration if there is at least a 90° angle along the axis of the root, whereas others defined dilaceration as a deviation from the normal axis of the tooth of 20° or more in the apical third of the root (Chohayeb, 1983). The prevalence of dilacerated roots amongst different tooth types as reported in the literature can be seen in Table 2 (Bodrumlu et al, 2012;Hamasha et al, 2002;Kuzekanani & Sadeghi, 2019;Ledesma-Montes et al, 2019;Malcic et al, 2006;Miloglu et al, 2010;Nabavizadeh et al, 2013;Udoye & Jafarzadeh, 2009). Although all highly curved canals might be described as dilacerated canals, the term dilaceration is frequently referred to root canals that combine an increased angle of curvature with a small radius of curvature.…”
Section: Anatomy-related Factorsmentioning
confidence: 99%
“…Moreover, increased length of the arc of curvature usually means a large radius. The shorter the length of curvature the more abrupt the deviation becomes at the same degree of curvature, hence representing a smaller radius of curvature (Gao T A B L E 2 Prevalence of root dilacerations amongst tooth types % (Bodrumlu et al, 2012;Hamasha et al, 2002;Kuzekanani & Sadeghi, 2019;Ledesma-Montes et al, 2019;Malcic et al, 2006;Miloglu et al, 2010;Nabavizadeh et al, 2013;Udoye & Jafarzadeh, 2009) Note: Higher prevalence is highlighted with red colour, followed by orange and green. Most studies agree that the prevalence of dilacerations is higher in mandibular third molars, followed by maxillary lateral incisors and maxillary premolars.…”
Section: Anatomy-related Factorsmentioning
confidence: 99%